Fabrication of photocatalytically active vanadium oxide nanostructures via plasma route. (30th April 2018) - Kajita, Shin; Yoshida, Tomoko; Ohno, Noriyasu; Ichino, Yusuke; Yoshida, Naoaki
Abstract: Plasma irradiation was used to create nanostructured vanadium oxide with potential commercial and industrial applications. Morphology changes were induced at the nano- and micro-meter scale, accompanied by the growth of helium nanobubbles. Micrometer-sized pillars, cube-shaped nanostructures, and fuzzy fiberform nanostructures were grown on the surface; the necessary conditions in terms of the incident ion energy and the surface temperature for those morphology changes were revealed. Hydrogen production experiments using a photocatalytic reaction with aqueous methanol solution were conducted on the fabricated samples. Enhanced H2 production was confirmed with the plasma irradiated nanostructured sample that had been oxidized in air atmosphere. Photocatalytically inactive vanadium oxide exhibited a high photocatalytic activity after nanostructurization of the surface by helium plasma irradiation.